TYPES OF INTERNSHIPS IN HIGHER EDUCATIONAL INSTITUTIONS OF DEVELOPED COUNTRIES (Eureka Journal of Language, Culture & Social Change, 2026)
In developed countries, practical training plays a crucial role in higher education by integrating theoretical knowledge with real-world experience. Various forms of practice, such as internships, laboratory and research training, dual education, project-based learning, and virtual simulations, help students develop professional skills, independent thinking, and adaptability to labor market demands. Effective organization of practical training enhances the quality of education and prepares competitive specialists.
Keywords: Higher education, practical training, internship, dual education, research practice, virtual simulation, professional skills.